Influence of pH in an Anaerobic Baffled Reactor for Treating Real Textile Dye Wastewater (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The wastewater discharged from the textile dyeing units contains the toxic level of chemicals in large quantity and cause severe setbacks in the healthy life of an eco system. The proper technologies need to be used for the treatment of wastewater before discharge into land or water course. The objective of this study is to evaluate the effective pH on microbial activity of anaerobic baffled reactor for treating textile wastewater. The pH is an important parameter which influenced the performance of the reactor. An experimental model was designed and conducted to study the impact of pH in the textile effluent. The pH acts as an important role for the efficient removal of COD which attains 91.67% with a HRT of 1.748 days at an OLR of 2.745 Kg COD/m3.day.